Achievement Improvement of Basic Table Tennis Techniques Through The Application of Audio-Visual Learning Media - Wijaya, Willy Bachtiar; Hasmyati, Hasmyati; Asran, Asran (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The goal of this study is to see if using audio-visual media in conjunction with a scientific approach to learning table tennis game activities at SMP Negeri 1 Kabuh in Jombang, Indonesia, may increase student learning outcomes and to see how far those aims have been accomplished. This study employs two cycles of classroom action research. Planning, action implementation, observation, analysis, and reflection are the four steps of each cycle. According to the outcomes of the analyses, cycles I and II resulted in a significant increase. The results of learning to play table tennis in the first cycle were 59.38 percent across the board, with 19 students finishing the course. In cycle II, the percentage of students with complete learning outcomes increased to 87.51 percent, while the percentage of students with incomplete learning outcomes increased to 28 percent. The percentage of students with complete learning outcomes increased by 100% during cycle III, while the percentage of students with incomplete learning outcomes climbed by 32%. As a result, learning through the use of audio-visual learning media can improve learning achievement in class VII students of public middle-school 1 Kabuh.